Are Stem Cells Derived from Synovium and Fat Pad Able to Treat Induced Knee Osteoarthritis in Rats?. (13th July 2020) - Zare, Reza; Tanideh, Nader; Nikahval, Behrooz; Mirtalebi, Maryam Sadat; Ahmadi, Nasrollah; Zarea, Shahrokh; Hosseinabadi, Omid Koohi; Bhimani, Rohan; Ashkani-Esfahani, Soheil
Abstract : Background . Osteoarthritis (OA) is a chronic disease and a significant cause of joint pain, tenderness, and limitation of motion. At present, no specific treatment is available, and mesenchymal stem cells (MSCs) have shown promising potentials in this regard. Herein, we aimed to evaluate the repairing potentials of stem cells derived from the synovium and fat pad in the treatment of OA. Methods . Twenty-eight male rats (220 ± 20   g, aged 10-12 weeks), were randomly divided into four groups (n = 7 ): C1: nontreated group, C2: Hyalgan-treated group, E1: adipose tissue-derived stem cell-treated group, and E2: synovial membrane-based stem cell-treated group. Collagenase type II was injected into the left knee; after eight weeks, OA was developed. Then, stem cells were injected, and rats were followed for three months. Afterward, specimens and radiological images were investigated. p value ≤ 0.05 was set as statistically significant. Results . Compared to the C1 group, the E1 and E2 groups showed significantly better results in all six pathological criteria as well as joint space width and osteophytes of medial tibial, medial femoral, and medial fabellar condyles (p ≤ 0.001 ). Similarly, compared to the C2 group, the E1 and E2 groups had better scores regarding surface, matrix, cell distribution, and cell population viability (p < 0.05 ). E2 showed considerably higher scores compared to C2 regarding subchondral bone and cartilage mineralization (p < 0.05 ). The joint space width was similar between the C2 and E groups. Conclusion . Treatment of OA with MSCs, particularly synovial membrane-derived stem cells, not only prevented but also healed OA of the knee to some extent in comparison to the Hyalgan and nontreatment groups.